Two tales of community work: Social workers’ experiences of role changes in the Netherlands and Norway - Aaslund, Håvard; Pruim, Eelke (Journal of Comparative Social Work, 2020)
Community-oriented approaches in social work are highlighted in both social work literature and policy documents in post-financial crisis Europe, and in the Nordic welfare states where professionalized bureaucracy, universal benefits and institutionalized social work have been the norm. The aim of this article is to explore social workers’ experiences of role changes in the transition to a more community-oriented approach, characterized by ambulatory work, the facilitation of local resources, multi-disciplinary collaboration and user participation. The empirical data consists of qualitative data from two cases: a political reform in the Netherlands (The Social Support Act), and a user-initialized project in Norway. Ten social workers from nine different organizations were interviewed in the Netherlands, and four social workers from one community-based project in Norway. We analysed these as a multiple case study of a transformation towards community-based practice, but one in which the political and organizational context differs. A common theme was the changing of the roles of the social worker and the subsequent experiences of challenges in different contextual settings. We present our findings under the topics of identity work, differing organizational expectations and role conflicts. Social workers in both the Norwegian and Dutch sample express experiences of multiple roles, vague roles and conflicting roles, with our analysis showing that role stress was common in both cases, regardless of whether the initiative was top-down or bottom-up. Remedying role stress could be a crucial element in processes aiming at user participation, social cohesion, cross-disciplinary cooperation and strengths perspectives.